Les noir est une couleur : Hommage vivant à Aimé Maeght. - Arnaud, Claude; Aumont, Jacques; Damisch, Hubert; Grammont, Claudine; Henric, Jacques; Kober, Jacques; Lascault, Gilbert; Lemaire, Gérard-Georges; Païni, Dominique; Risset, Jacqueline; Semin, Didier; Exhibition. Le noir est une couleur : Hommage vivant à Aimé Maeght. Fondation Maeght Saint-Paul. 2006-06-30. 2008-11-05 (Saint-Paul : Fondation Maeght Saint-Paul, 2006)
Agam, Yaacov ; Andre, Carl ; Arman ; Arp, Hans (Jean) ; Art & Language ; Baselitz, Georg ; Ben ; Bertrand, Jean-Pierre ; Blais, Jean-Charles ; Bloch, Pierrette ; Boetti, Alighiero ; Boltanski, Christian ; Bonnard, Pierre ; BP ; Braque, Georges ; Buraglio, Pierre ; Burri, Alberto ; Bury, Pol ; Byars, James Lee ; Calder, Alexander ; Chardon, Nicolas ; Chillida, Eduardo ; Convert, Pascal ; Debré, Olivier ; Degottex, Jean ; Delprat, Hélène ; Dion, Mark ; Dubuffet, Jean ; Emmanuel ; Ernst, Max ; Favier, Philippe ; Fiedler, François ; Fischl, Eric ; Fleischer, Alain ; Fontana, Lucio ; Foucault, Henri ; Gasiorowski, Gérard ; General Idea ; Giacometti, Alberto ; Gianikian, Yervant ; Hantaï, Simon ; Hartung, Hans ; Henrot, Camille ; Jackson, Richard ; Kandinsky, Wassily ; Kelly, Ellsworth ; Kiefer, Anselm ; Kline, Franz ; de Kooning, Willem ; Kounellis, Jannis ; Kuroda, Aki ; Lebel, Jean-Jacques ; Leger, Fernand ; LeWitt, Sol ; Malaval, Robert ; Marden, Brice ; Marfaing, André ; Mariën, Marcel ; Masson, Andre ; Matisse, Henri ; McCollum, Allan ; Michaux, Henri ; Miro, Joan ; Moninot, Bernard ; Morellet, François ; Motherwell, Robert ; Muniz, Vik ; Nemours, Aurélie ; Nevelson, Louise ; Newman, Barnett ; Ouzani, Mélik ; Pagès, Bernard ; Paik, Nam June ; Parmiggiani, Claudio ; Picasso, Pablo ; Pinaud, Pascal ; Poirier, Anne & Patrick ; Rainer, Arnulf ; Raysse, Martial ; Re, Marco Del ; Recalcati, Antonio ; Reigl, Judit ; Reinhardt, Ad ; Ricci Lucchi, Angela ; Richter, Gerhard ; Rouan, François ; Saura, Antonio ; Serra, Richard ; Shiraga, Kazuo ; Skoda, Vladimir ; Smith, Kimber ; Smith, Tony ; de Soria, Claude ; Soto, Jesus Rafael ; Soulages, Pierre ; Stephant, Didier ; Tal-Coat, Pierre ; Tàpies, Antoni ; Tinguely, Jean ; Ubac, Raoul ; Vandercam, Serge ; etc.
biog. p. 234-263
Engels
Frans
boek